PALINOLOGIA DEL SILURICO SUPERIOR (FORMACION LOS ESPEJOS) DE LA QUEBRADA DE LAS AGUADITAS, PRECORDILLERA DE SAN JUAN, ARGENTINA (Ameghiniana, 2013)
The microplankton found in the middle lo upper section of Los Espejos Formation (Upper Silurian) in the Quebrada de las Aguaditas, SW of Jáchal is described in the present contribution. There are given the dislribution of the species in the column section and the chronological range. The acritarch assemblages are compared with other assemblages of similar age from the same region and from the world. From the correlation with the microplankton of other world regions, analogies with assemblages from gondwanic and perigondwanic areas are establi shed. The palynofacies distribution, parallel to the paleolatitudes, proposed for the Silurian is discussed. The microplankton has been assigned to the Upper Ludlovian-Pridolian? The relation between the paleoenvironmenl of deposition and the distribution and preservation of the palynomorphs is analized.